Underpinning Hawley’s Risk Theory of Profit on Risk Intelligence and Sustainability Relations of SMEs in Nigeria - Murtala Garba; Fauzilah Salleh; Usman Ahmed Hafiz (Ilomata International Journal of Management, 2022)
Sustainable development is one of the topical issues posing a global challenge to the business world. To remain successful in today's competitive business environment, Small and Medium-Scale Enterprises (SMEs) must find a way to exist by adapting to dynamic sustainability challenges. The study aimed to examine Hawley’s Risk Theory of Profit's underpinning role in explaining the connection between Risk Intelligence (RI) and SMEs’ sustainability (SUS). It was understood that risk could pose both opportunities and threats to business, and therefore, proactive detection is paramount to address the risk capable of ridiculing sustainability. Therefore, we proposed integrating the moderating role of financial performance in the relationship between Nigerian SMEs' risk intelligence and sustainability. The study found Hawley’s theory relevant to risk and sustainability tradeoff. Previous studies proxied risk intelligence by knowledge management, financial literacy, and risk-taking propensity, which paved the way for developing a framework for attaining sustainable SMEs in Nigeria. We concluded that SME’s sustainability could be ensured by effectively managing inherent risks and should be incorporated into Enterprise Risk Management (ERM) systems.